The Growth Story of the 21st Century - Stern, Nicholas (LSE Press, 2026)
The world stands at a crossroads. The next decade will determine whether we avoid climate, biodiversity, and economic catastrophe – or unlock a new era of sustainable, resilient, and inclusive growth. The Growth Story of the 21st Century challenges the outdated idea that we must choose between climate action and development. Instead, it presents a compelling case for a transformation that delivers both prosperity and a healthier planet. Drawing on economics, finance, policy, politics, and behavioural science, Nicholas Stern explores why this transformation is essential, what it entails, and how we can achieve it. He revisits the insights of the Stern Review two decades on and sets out a new research agenda for economics and the social sciences. This is a story of optimism – about how rapid technological advances, including digitisation and AI, can drive change at scale. But it does not shy away from the immense challenges ahead. With clear and practical strategies for national and international action, this book is a call to leaders, businesses, and individuals alike: the future is in our hands, and delay is the riskiest option of all.